ChemInform Abstract: Near UV‐Pumped Bluish‐White Emitting K(Ba, Sr, Ca)BP2O8:Eu2+ Phosphors. Issue 40 (12th September 2013) - Su, Shaodong; Liu, Wei; Duan, Ruijing; Cao, Lixin; Su, Ge; Zhao, Chenggong
Abstract A series of Eu2+‐doped K(Ba, Sr, Ca)BP2O8 phosphors is prepared by solid state reaction of stoichiometric mixtures of K2CO3, BaCO3, H3BO3, NH4H2PO4, SrCO3, CaCO3, and Eu2O3 (1.